Cephalopod fauna in the Southern Ocean using the diet of wandering albatrosses Diomedea exulans:a stable isotopes approach - Guerreiro, Miguel Fernandes, 1989- (2012)
Tese de mestrado. Biologia (Ecologia Marinha). Universidade de Lisboa, Faculdade de Ciências, 2012